Prevalence and distribution of recurrent aphthous stomatitis in 10-13 years old: observational study in elementary school - Probosari, Niken; Syifa, Nur ‘Aini; Budirahardjo, Roedy; Prihatiningrum, Berlian; Sulistiyani, Sulistiyani; Setyorini, Dyah; Sukanto, Sukanto (Universitas Padjadjaran, 2023)
ABSTRACT Introduction: Recurrent aphthous stomatitis (RAS), better known as canker sore, is the most common soft tissue disease of the oral cavity and affects 5 to 66% of the world’s population. RAS often begins in childhood and the age group of 10-14 years has the highest proportion of RAS in children. The purpose of this study was to determine the prevalence and distribution of RAS according to gender and age, clinical characteristics, ulcer location, and predisposing factors in 10 to 13 years old students. Methods: This observational study used cross-sectional design with total sampling method. The data were collected by oral cavity examination using direct observation with a mouth mirror and by filling out 10 closed questions questionnaires about predisposing factors of RAS. The data that had been obtained was tabulated and presented in tabular form using SPSS 16.0. Results: With a total sample size of 79 students from 10-13 years old, this study showed that the prevalence of RAS was found in 16 students (20,25%). The distribution of RAS based on gender was found to be higher in females (11,39%), while based on age, it was found that 11 years of age was the age that suffered the most RAS (10,13%). Based on clinical examination, all of the subjects were categorized as minor, mostly found at labial mucosa and tongue (31,25%). Based on questionnaires, the highest predisposing factor was due to trauma in 11 people (68,75%). Conclusion: In our study, among 10 to 13 year old students with RAS, females were mostly found at 11 years of age, detected with minor clinical characteristics. The labial mucosa and tongue, and trauma were the highest predisposing factors.KEYWORDS: recurrent aphthous stomatitis, children, prevalence, distribution